KAJIAN PEREKONOMIAN MASYARAKAT MELALUI USAHA KERAJINAN TIKAR PANDAN DI DESA PAMOTAN KABUPATEN LAMONGAN - Syamsul Arifin; Eka Ramiati (AT TAMKIN : Jurnal Pengembangan Masyarakat Islam dan Perubahan Sosial, 2021)
This study aims to find out how the history of the beginning of the pandan mat as an instrument for community development and to find out the development processes that initially experienced difficulties in the economic conditions of the community. They try to get a better life and prosperity together by taking advantage of everything that is available in their homeland. This research was collected through observation, interviews, and documentation. With a deductive-induction mindset, the results of this study conclude that the development process that occurs begins with the provision of skills that Mbah Darmi passed on to her daughter, friends and neighbors. until finally developing almost all citizens of the community to pursue the craft of woven mats made of pandanus. Driven by the motivation to continue to get a better life that makes the surrounding community persist in being craftsmen of woven pandanus mats to this day.